Dietary patterns in Mexican preschool children are associated with stunting and overweight - Mario E. Flores; Marta Rivera-Pasquel; Nayeli Macías; Luisa María Sánchez-Zamorano; Sonia Rodríguez-Ramírez; Alejandra Contreras-Manzano; Edgar Denova-Gutiérrez (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To evaluate the association between dietary patterns, stunting, and overweight among Mexican preschoolers. METHODS This study was conducted with anthropometric (weight, height/length), sociodemographic (age, gender, education level of household head, socioeconomic status, country region and area, ethnicity, and beneficiary of social programs), and dietary data (Semiquantitative-food frequency questionnaire) on children aged from 1 to 4 years collected from the Mexican National Health and Nutrition Survey-2012. Dietary patterns were derived by principal components analysis. The association between dietary patterns, stunting, and overweight was assessed by prevalence ratios (PR), estimated by Poisson regression. RESULTS In total, 1,112 preschoolers (mean age 3.06 years, SD = 1.08 years; 48.8% females) were included in the study; 11.9% of whom presented stunting, and 6.7% overweight. We identified four dietary patterns: Fruits and Vegetables [F&V], Western [W], Traditional [T], and Milk and Liquids [M&L]. Considering the lowest tertile of each dietary pattern as reference, the prevalence of stunting was 2.04 times higher [95%CI: 1.17-3.56] among children in the highest tertile of the "F&V" pattern. The prevalence of stunting was lower among children in the highest tertile of the "W" pattern [PR = 0.48; 95%CI: 0.27-0.85]. Overweight was negatively associated with the "F&V" dietary pattern [PR = 0.37; 95%CI: 0.16-0.85 for its highest tertile], and children whose consumption was mostly equivalent to the "T" pattern showed higher prevalence of stunting [PR = 1.74; 95%CI: 1.01-3.00]. CONCLUSIONS The prevalence of stunting and overweight in a nationwide sample of Mexican preschoolers was associated with dietary patterns.